Prospective evaluation of the proportion of sessile serrated adenoma/polyps in endoscopically diagnosed colorectal polyps with hyperplastic features - Sano, Wataru (© Georg Thieme Verlag KG, 2015)

(untitled) (Endosc Int Open)
Background and study aims: Sessile serrated adenoma/polyps (SSA/Ps) are considered precursors of colorectal cancers with microsatellite instability. However, it is still difficult to differentiate SSA/Ps from hyperplastic polyps endoscopically; therefore, the prevalence of SSA/Ps remains uncertain in clinical practice. This study aimed to clarify the proportion of SSA/Ps in endoscopically diagnosed colorectal polyps with hyperplastic features (E-HPs). Patients and methods: Patients aged ≥ 40 years undergoing colonoscopy for standard clinical indications at our center were prospectively enrolled between June 2013 and May 2014. During colonoscopy, 0.05 % indigo carmine dye was sprayed throughout the colorectum to highlight lesions. All detected lesions were diagnosed by high definition magnifying narrow-band imaging and were resected endoscopically or surgically, apart from rectosigmoid E-HPs ≤ 5 mm. The number of rectosigmoid E-HPs ≤ 5 mm was recorded, and some were resected for use as tissue samples. Results: A total of 343 patients (male: 42.9 %; mean age: 61.5 years) were included. Among 3838 E-HPs (distal: 96.4 %) detected in 294 patients, 792 were resected and analyzed. All of 21 SSA/Ps identified in 17 patients were included in E-HPs, and the overall proportion of SSA/Ps in E-HPs was 2.7 %. However, this proportion increased with the size of E-HPs (≤ 5 mm: 0.7 %; 6 – 9 mm: 29.0 %; ≥ 10 mm: 70 %) and was higher in the proximal colon than in the distal colorectum (10.9 % vs. 0.9 %). In addition, no SSA/P was found in the rectum, and no SSA/P had cytological dysplasia. Conclusions: The overall proportion of SSA/Ps in E-HPs was 2.7 %, although this proportion was higher in the proximal colon and increased with the size of E-HPs. SSA/Ps were common in routine colonoscopy, with a prevalence of at least 5.0 %. Study registration: UMIN000010832.